The complete mitochondrial genome and phylogenetic analysis of Spondylus violaceus. Issue 2 (3rd July 2019) - Liu, Fuyun; Li, Yuli; Liu, Jing; Zhang, Yuehuan; Bao, Zhenmin; Wang, Shi
Abstract: Spondylus violaceus is a species of the bivalve family Spondylidae, commonly known as thorny oyster. Here, we report the complete mitochondrial genome of S. violaceus . The mitochondrial genome of S. violaceus is 30, 160 bp in length, which contains 12 protein-coding genes, 2 ribosomal RNA genes and 19 transfer RNA genes. The overall AT content (58.31%) was higher than GC content (41.69%). This is the first record of complete mitochondrial genome in the family Spondylidae, providing the basis for future taxonomic and phylogenetic studies of this bivalve family.